Si-cology 101 : tales & wisdom from Duck Dynasty's favorite uncle - Robertson, Si, 1948- (New York : Howard Books, 2013)
You know him from the hit A&E show "Duck Dynasty." Now you can enjoy Uncle Si's tall tales, crazy exploits, and quirky one-liners in one raucous collection. Uncle Si has a limitless supply of stories about his childhood, duck hunting adventures, his days in Vietnam, and everything in between. Now the best of those tales are gathered into this roaring book. And as Uncle Si recounts his outlandish tales, he weaves in an up-close look into his personal life. You'll learn about his childhood life as the youngest son in the Robertson family, his college days, and his time in Vietnam. And in many of these never- before-heard tales, Si openly talks about his wife Christina and two children, Scott and Trasa who are never seen and rarely mentioned on the show
On the show Duck dynasty, Uncle Si has a limitless supply of stories about his childhood, duck hunting adventures, his days in Vietnam, and everything in between. Now the best of those tales are gathered into this roaring book. As you learn about his behind-the-scenes life, this smattering of zany stories will have you falling over with laughter and retelling them to all your friends
A star of the hit A&E show "Duck Dynasty" brings together his best tall tales, crazy exploits, and quirky one-liners in a single collection
Prologue -- Birthday suit -- Dynamic dog duo -- Redneck pets -- Book report -- Unidentified walking object -- Snake bit -- Floating log -- Dancing with wolves -- Bumblebees -- Kamikaze pilot -- C is always the best answer -- Big oaf -- Passing the test -- Good morning, Vietnam! -- Deuce and a half -- Guard duty -- Leave it to beavers -- Black market -- Iced tea glass -- The woman of my dreams -- Newlyweds -- God's blessing -- Trasa -- Like father, like son -- Sleepwalking -- Mass murder -- Semiretirement -- Homecoming -- Broken heart -- Faith -- Afterword: Letters to Si from his family
Keywords: Robertson, Si, -- 1948-; Television personalities -- United States -- Biography